Artistic Feature of Alisher Navoi's "Farhod and Shirin": Fitur Artistik "Farhod dan Shirin" Alisher Navoi - Hayitov Shavkat Ahmadovich; Sayidova Shahruza Sohibovna (Academia Open, 2022)
Hazrat Alisher Navoi's epic "Farhod and Shirin" discusses many topical issues and universal issues related to the long past, life and future of the XV century. The poet skillfully used the arts of classical poetics, such as tazod (antithesis), talmeeh, tashbeeh, tanosub (the art of proportion), mubolaga (hyperbole), and metaphor, to illuminate these issues and interpret goals and ideas. In Farhod and Shirin, the artistic means of expression served to give a vivid, effective expression of the ideas expressed in the epic, to convey the images clearly and vividly, to ensure the verbal elegance and eloquence of the masnavi verses. The article draws important scientific conclusions by examining the interrelationships between the arts and the imagery in Farhod and Shirin.